2019
DOI: 10.1111/joca.12264
|View full text |Cite
|
Sign up to set email alerts
|

The Financial Services Environment and Schools' Savings Rates in the San Francisco Kindergarten to College Program

Abstract: Children's savings accounts (CSAs) have emerged as a promising intervention to improve educational outcomes, curtail rising student loan debt, and promote equality of opportunity. Numerous localized CSA programs have emerged in the last decade, and many are embedded within school systems. This study leverages novel data to investigate participation in one of the oldest and most well‐known CSA programs in the country: the San Francisco Kindergarten to College (K2C) Program in the San Francisco Unified School Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…Thus, no introduced legislation has sought to specifically target minority populations and communities that are disproportionally represented among the unbanked and underbanked (FDIC, 2020 ). The missing illustrative mechanisms related to the goal of expanding access to bank accounts are notable because all have received attention in the research literature as critical to reducing the number of unbanked and underbanked (Center for Popular Democracy, 2013 ; Friedline et al, 2020 ), in particular, bank branch location and density of banks relative to Alternative Financial Services (Friedline et al, 2019a , b ). Regarding consumer protection and disclosure, there were no items related to protecting and strengthening the CFPB, which provides important consumer advocacy for individual consumers related to the banking industry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, no introduced legislation has sought to specifically target minority populations and communities that are disproportionally represented among the unbanked and underbanked (FDIC, 2020 ). The missing illustrative mechanisms related to the goal of expanding access to bank accounts are notable because all have received attention in the research literature as critical to reducing the number of unbanked and underbanked (Center for Popular Democracy, 2013 ; Friedline et al, 2020 ), in particular, bank branch location and density of banks relative to Alternative Financial Services (Friedline et al, 2019a , b ). Regarding consumer protection and disclosure, there were no items related to protecting and strengthening the CFPB, which provides important consumer advocacy for individual consumers related to the banking industry.…”
Section: Discussionmentioning
confidence: 99%
“…Other policies would expand access to banking and financial services in underserved communities through additional branches, changing the regulatory emphasis, and strengthening the physical infrastructure through which banking is delivered. Policy that promotes bank branch location in underserved communities could allow for easier account access (Friedline et al, 2019a , b ), as would increasing the sheer number of bank branches so that bank branches outnumber more costly non-bank financial institutions offering AFS in underserved communities (Friedline et al, 2019a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…A set of mutually reinforcing policies and practices have created spatial arrangements whereby higher-cost, lowerquality financial services are expanding and disproportionately locating in economically distressed and racially marginalized communities (15,16,(56)(57)(58)(59)(60)(61)(62)(63)(64). Examining the locations of payday lenders in Colorado in 2007, a year when the state passed new legislation regulating payday loans, Gallmeyer and Roberts found that payday lender storefronts were disproportionately concentrated in census block groups with lower median incomes and higher poverty rates (62).…”
Section: The Locations Of Payday Lender Storefrontsmentioning
confidence: 99%
“…Similar to redlining in the lending market, policymakers' decisions to deregulate the banking industry discouraged black and brown communities' access to financial services by precipitating a decline of “brick‐and‐mortar” branches (Brown et al ., 2016; Celerier and Matray, 2016). Bank branches were sparsely located in communities of color and lower‐income white communities to begin with (Fowler et al ., 2014; Rockoff, 2018; Traweek and Wardlaw, 2018), and their declines amplified the racialized geography of financial services (Brown et al ., 2016; Celerier and Matray, 2016; Friedline and Despard, 2017; Friedline et al ., 2019). For example, some communities of color lost half their branches since the Great Recession (Apgar and Herbert, 2006; Celerier and Matray, 2016; Kashian and Drago, 2017; Toussaint‐Comeau and Newberger, 2017), and 20% of branches are projected to close over the next decade (JLL, 2017; Ensign et al ., 2018).…”
Section: A History Of Redlining In Financial Servicesmentioning
confidence: 99%
“…The number of payday lenders, check cashers, and other similar higher‐cost alternative financial services has increased substantially since the 1980s and 1990s (Caskey, 1994; Apgar and Herbert, 2006), and this industry makes an annual profit of $300 billion by charging exorbitant interest rates and fees to lower‐income consumers with limited credit histories (Federal Deposit Insurance Corporation, 2009). The growth of higher‐cost alternative financial services has been concentrated in black and brown communities (Fowler et al ., 2014; Baradaran, 2015; Friedline and Despard, 2017; Friedline and Kepple, 2017; Faber, 2017a, 2019; Friedline et al ., 2019). At the county level, for instance, increases in the number of payday lenders per capita are associated with increases in a county's black population (Fowler et al ., 2014).…”
Section: A History Of Redlining In Financial Servicesmentioning
confidence: 99%